The Relationship Between Fatigue, Family Support, and Quality of Life in Patients Undergoing Hemodialysis - Almira Hulwani; Rima Berti Anggraini; Maryana Maryana (Genius Journal, 2027)
Introduction : Patients with chronic kidney disease undergoing hemodialysis commonly experience a decline in physical and psychosocial functioning, which negatively impacts their quality of life. One of the main issues frequently encountered is chronic fatigue, as well as weak family support, which should serve as a key pillar in helping patients adapt to their chronic condition. Objective: This study aimed to determine the relationship between fatigue and family support with the quality of life of chronic kidney disease patients undergoing hemodialysis at Bakti Timah Hospital Pangkalpinang in 2025. Method: This research used a quantitative analytic design with a cross-sectional approach. The sample consisted of 36 respondents selected using total sampling. The instruments used in the study were fatigue, family support, and quality of life questionnaires. Data were analyzed using the Chi-Square statistical test with a significance level of α = 0.05. Result: The results showed a significant relationship between fatigue and quality of life (p = 0.016; POR = 4.094; 95% CI: 1.385–12.104), and also a significant relationship between family support and quality of life (p = 0.033; POR = 0.771; 95% CI: 0.269–2.208). These findings indicate that the lower the fatigue level and the stronger the family support, the better the patient's quality of life Conclusion: The conclusion of this study is that both fatigue and family support play an important role in the quality of life of chronic kidney disease patients undergoing hemodialysis. Promotive and preventive efforts in fatigue management and increased family involvement are highly recommended in nursing practice